Pain & Inflammation: Effects of short term daily adminstration of Vitamin B12 & Folic acid in long evans rats - Imtiaz, Masud; Begum, Noorzahan; Ali, Taskina; Gomes, Richmond Ronald; Saha, Sanjoy; Tasfi, Riza Faridun; Ahmed, Khan Shakil; Kamal, Nahid (Bangladesh Critical Care Journal, 2016)
Background : Vitamin B12 & Folic acid (FA) are used with other B vitamins to relieve various painful and inflammatory conditions. But combined effects of vitamin B12 & FA on nociceptive pain, inflammatory pain and inflammation are yet to be clearly demonstrated. Objective: To assess the effectiveness of short term daily administration of B12 & FA on reducing pain and inflammation. Methods: This prospective experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from 1st January 2011 to 30th June 2012. For this purpose, 12 male Long Evans rats, weighing 200 to 250 grams were collected from the animal house of BIRDEM, Shahabag, Dhaka. All the rats received a daily intraperitoneal injection of either combination of B12 (15mg/kg) & FA (5mg/kg) or equal volume of normal saline for 7 consecutive days. To evaluate the effects on pain, tail immersion test for nociceptive pain and formalin test for nociceptive & inflammatory pain were done. In addition, to evaluate their effects on inflammation formalin induced hind paw oedema was measured. Results: Combination of B12 & FA Supplementation significantly lowered the variables for inflammatory pain & inflammation. Conclusion: This study revealed that, combined short term daily supplementation of B12 & FA is effective in lowering inflammatory pain & inflammation. Bangladesh Crit Care J March 2016; 4 (1): 33-37